“Social Cognition And Work Behaviour In Schizophrenic Patients” - Narsinhbhai V. Chaudhary; Dr. Yogesh R. Pandya (Educational Administration: Theory and Practice, 2024)
The aim of the present study was to understand the social cognitions and work behavior patterns of schizophrenic patients. A total sample of 30 participants, 15 male and 15 female patients with schizophrenia, was recruited from Ahmadabad, Gujarat. Schizophrenic participants were screened using PANSS. The Edinburg Social Cognition Test is used to measure social cognition, and the Work Behaviour Inventory is used to measure work behaviour. For analysis, descriptive statistics, the t test, and correlation were used. The result found no significant difference in social cognition as well as in work behavior, but the present study found positive relationships between social cognitions and work behavior